Mapping the Potential of Zakat Collection Digitally in Indonesia - Alvina Syafira Fauzia; Sri Mulatsih; Findi Alexandi (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
The rapid development of technology in the financial sector encourages the transformation of zakat payment from a conventional system to a digital one. However, there are several obstacles in realizing the digitization of zakat in Indonesia, both from the internal and external side of zakat management organizations (OPZ). Therefore, a strategy is needed to support the digitization of zakat. This study aims to map the potential of collecting zakat through digital means in Indonesia. It is hoped that through this research, it could describe the potential conditions of each province and become a useful blueprint in formulating zakat policies in Indonesia. The data used in this study is secondary data from BPS, Puskas Baznas and Census for 2019 period. The method used in the mapping process is K-means Cluster, while the calculation of digital zakat potential uses the Exploratory Data Analysis (EDA) method. The results of this study show that the mapping is divided into 3 clusters where cluster 1 consists of 30 provinces, cluster 2 consists of 3 provinces and cluster 3 consists of 1 province. By dividing the high, medium and low categories for each variable in every cluster, the strengths and weaknesses in each of the variables for digital zakat potential can be assessed. Further, the estimation of potential for zakat collection through digital means in Indonesia is estimated at 5,32 trillion rupiah per month or 63,93 trillion rupiah per year in 2019 where West Java Province is the province with the highest digital zakat potential. The conclusion of this research is the importance of synergies between zakat management organizations (OPZ), the community and the government. There is need to pay attention to the weaknesses and strengths of each variable per province for optimizing zakat collection through digital means in Indonesia.